2021
DOI: 10.1029/2020jd034411
|View full text |Cite
|
Sign up to set email alerts
|

Combined Optical and Radio‐Frequency Measurements of a Lightning Megaflash by the FORTE Satellite

Abstract: The optical and VHF instrumentation on the fast on‐orbit recording of transient events (FORTE) satellite is used to document the combined phenomenology evolution of a lightning “megaflash”—Mesoscale lightning that propagates laterally over exceptional distances. We identify a FORTE flash whose maximum extent was 82 km and inferred length over multiple distinct branches exceeded 100 km. This flash lasted 1.2 s and produced 250 optical and 591 radio frequency events. We find that the channel development mapped b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 50 publications
(93 reference statements)
0
25
0
Order By: Relevance
“…Figure 3e shows a 2D histogram of the inter‐event interval after the event of interest. If the simple event occurred as part of a long‐lived process (as in Figure 5 in Peterson et al., 2021), then the inter‐event interval would be ∼4.4 ms (bottom horizontal gray line in Figure 3e). If the next event occurred as part of a different process but still in the same flash, then the inter‐event interval would occur above the bottom horizontal line and below the middle gray line at 330 ms.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3e shows a 2D histogram of the inter‐event interval after the event of interest. If the simple event occurred as part of a long‐lived process (as in Figure 5 in Peterson et al., 2021), then the inter‐event interval would be ∼4.4 ms (bottom horizontal gray line in Figure 3e). If the next event occurred as part of a different process but still in the same flash, then the inter‐event interval would occur above the bottom horizontal line and below the middle gray line at 330 ms.…”
Section: Resultsmentioning
confidence: 99%
“…Low‐altitude sources are found to be particularly common in winter and/or oceanic regions outside of the tropics, as well as over the La Plata basin, where large MCSs produce abundant stratiform lightning, including megaflashes. We previously showed that an individual large stratiform flash can produce hundreds of FORTE RF events with impulsive VHF sources clustered in a layer between 4 and 8 km altitude (Peterson et al., 2021a). Regions with frequent stratiform lightning are thus expected to have source altitude profiles with significant contributions from both high‐altitude convective sources and low‐altitude stratiform sources.…”
Section: Discussionmentioning
confidence: 99%
“…We used it previously to identify interesting flashes in Peterson et al. (2021a, 2021b), and to generate event and flash statistics in Peterson (2022a, 2022c).…”
Section: Methodsmentioning
confidence: 99%
“…This data set is documented at length in Peterson et al. (2021a) and the components of the data set that we will use in this study are described in the following sections. See Jacobson et al.…”
Section: Methodsmentioning
confidence: 99%
“…Whenever a specified number of PDD events is recorded (i.e., a multiple of 10) during a specified time interval, the PDD will turn off until the next GPS-derived 1 Hz signal. We have discussed PDD dropping out after precisely 20 triggers in both FORTE flashes that we previously analyzed in detail in Peterson et al (2021aPeterson et al ( , 2021b due to this filter. It will only activate in periods with high lightning rates (including high event rates from individual flashes), and the instrument should be able to recover at the next GPS second, with only triggers in the middle of the flash being missed.…”
Section: Forte Pdd Eventsmentioning
confidence: 98%